Functionalized non-spherical powder raw materials and their preparation methods
Through mechanical milling and/or chemical milling, the forged metal alloy is converted into non-spherical particles and assembled functionalized particles on its surface, solving the problem of high material costs in the prior art and achieving low-cost and efficient powder metallurgy Craft.
Patent Information
- Application Number
- CN202080080111.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-19
- Filing Date
- 2020-09-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-09-20
AI Technical Summary
In existing powder-based additive manufacturing and powder metallurgy processes, the material costs are high, limiting the practicality and implementation of the process.
Mechanical milling and/or chemical milling are used to convert the forged non-weldable metal alloy raw materials into non-spherical particles, and functionalized particles are physically and/or chemically assembled on the surface of these particles to form a functionalized material containing metals.
Through this method, the cost of materials can be effectively reduced, low-cost forged metal alloy raw materials can be used, and the process avoids expensive gas or water atomization processes, improving the economic and feasibility of the process.
Smart Images

Figure CN114728332B_ABST
Abstract
Description
[0001] Priority data
[0002] This international patent application claims priority to U.S. Provisional Patent Application No. 62 / 936,713 filed on November 18, 2019 and U.S. Patent Application No. 17 / 026,218 filed on September 19, 2020, each of which is hereby incorporated by reference herein. Field of the Invention
[0003] The present invention generally relates to powder-based additive manufacturing processes and other powder-based metallurgical processes, and metal-containing functionalized materials that can be used in these processes. Background of the Invention
[0005] Metal-based additive manufacturing or three-dimensional (3D) printing has applications in many industries, including the aerospace and automotive industries. Building metal parts layer by layer increases design freedom and manufacturing flexibility, enabling complex geometries while eliminating traditional economies of scale constraints. In metal-based additive manufacturing, applying a direct energy source (such as a laser or electron beam) to melt the alloy powder locally results in solidification rates between 0.01m / s and 5m / s, which is an order of magnitude higher than conventional casting processes.
[0006] Additive manufacturing allows for the manufacture of complex parts of any design in a single step. Additive manufacturing eliminates the need to assemble multiple parts while minimizing manufacturing time and the waste of material and energy typically associated with traditional manufacturing (such as machining or forging). While additive manufacturing is growing rapidly to produce metal, polymer and ceramic parts, the production of metal parts is its fastest growing area.
[0007] Commercial powder metallurgy processes typically employ gas atomization or water atomization to melt powders, where the particle morphology is controlled during the atomization process to exhibit spherical or near-spherical geometry. For example, in a powder bed metal additive manufacturing process, a spherical, atomized, monodispersed powder feedstock is used to control the flow of the powder. Multiple thin layers of powder are spread over a surface, melted, and solidified.
[0008] The use of gas atomized or water atomized metal alloy feedstock powders is well known. See Liu et al., "Preparation of superfine-grained high entropy alloy by spark plasmasintering gas atomized powder," Intermetallics 68 (2016) 16-22; and Murr et al., "Characterization of titanium aluminide alloy components fabricated by additive manufacturing using electron beam melting," Acta Materialia 58 (2010) 1887-1894, which are hereby incorporated by reference. These feedstocks are formed by starting from a melt and ejecting liquefied material into a controlled fluid stream through a specially designed nozzle. When exposed to a second fluid, the liquefied metal undergoes a phase change and solidifies, collecting at the bottom of the chamber or in a secondary containment vessel. The powder formed in this manner is then sieved to remove any oversized or undersized material, resulting in a low yield of approximately 25%-35% based on the input material.
[0009] Despite the unique thermochemical processing conditions of additive manufacturing or other powder metallurgy processes, the feedstock powders are usually selected from traditional cast or wrought alloys. Gas atomization has historically been the only way to obtain these alloy feedstocks in powder form.
[0010] However, it is well known that melt atomizing fine (less than 65 microns) and monodisperse (15-60 microns) spherical powders from bulk ingots is very expensive compared to conventional subtractive manufacturing processes. As an example, the cost of aluminum alloys is typically $2-5 / kg, depending on the composition, while atomized aluminum powders are only available industrially at a high cost of $45-300 / kg. To date, the significant price difference between raw materials and atomized powders has limited the practicality and implementation of metal additive manufacturing and relegated it to prototypes or high-margin parts (e.g., satellite or spacecraft structures) where manufacturing cost is not an important design driver.
[0011] However, in many commercial applications, performance and cost are considered equivalent or nearly equivalent design drivers. A paradigm shift is indeed needed to break the current trade-off involving material cost and part performance in powder-based additive manufacturing and other powder metallurgy processes. SUMMARY OF THE INVENTION
[0013] The present invention addresses the above-identified needs in the art, as will now be summarized and then further described in detail below.
[0014] Some variations provide a metal-containing functionalized material comprising:
[0015] (a) a plurality of non-spherical particles comprising a metal or a metal alloy; and
[0016] (b) a plurality of microparticles physically and / or chemically assembled on the surface of the non-spherical particle (i.e., functionalized microparticles), wherein the microparticles are selected from the group consisting of metals, metal alloys, metal carbides, metal nitrides, metal borides, metal hydrides, metal oxides, metal sulfides, ceramics, and combinations thereof,
[0017] wherein the microparticles are compositionally different from the non-spherical particles, and
[0018] The particles have an average particle size that is different from an average non-spherical particle size of the non-spherical particles.
[0019] In some embodiments, the non-spherical particles are selected from whiskers, needles, rods, fibers, debris, deformed ribbons, oblate spheroids, prolate spheroids, parallelepipeds, rhombuses, rectangular prisms, flakes, polyhedral particles, randomly shaped particles, and / or combinations thereof.
[0020] In some embodiments of metal-containing functionalized materials, non-spherical particles are characterized by a packing efficiency of from 40% to 65%, such as 40%-49%, 49%-55%, 55%-60% or 60%-65%. In certain embodiments, the packing efficiency is less than 64%. In the case of certain random shapes, the packing efficiency is less than 40%. In certain embodiments, a combination of shape and size results in a packing efficiency of >65%.
[0021] The non-spherical particles can be characterized by a median particle size (D50) of from 5 micrometers (μm) to 10 millimeters (mm), such as for the largest particle axis. For example, the median particle size can be in the range of 15-45 μm, 40-70 μm, 70-125 μm, 125-300 μm, 300-600 μm, or 600-10000 μm.
[0022] The average functionalized particle size can be, for example, from 5 nanometers (nm) to 100 μm. Typically, the average particle size is smaller than the average non-spherical particle size. In some embodiments, the average particle size is at least one order of magnitude smaller than the average non-spherical particle size. In other embodiments, the average particle size is equal to or greater than the average non-spherical particle size.
[0023] In some embodiments, the microparticles form a continuous coating on the non-spherical particles. In other embodiments, the microparticles form a discontinuous coating on the non-spherical particles.
[0024] In some embodiments, the non-spherical particles contain a metal selected from the group consisting of aluminum, titanium, cobalt, chromium, iron, copper, tungsten, magnesium, niobium, nickel, tantalum, silicon, vanadium, gold, silver, platinum, palladium, iridium, rhenium, zinc, cerium, molybdenum, zirconium, hafnium, and alloys or combinations thereof. Additional alloying elements may also be present.
[0025] In some embodiments, the microparticles contain a metal selected from the group consisting of aluminum, titanium, cobalt, zinc, tin, chromium, bismuth, neodymium, dysprosium, erbium, samarium, praseodymium, gadolinium, ytterbium, lanthanum, boron, lithium, calcium, strontium, scandium, yttrium, manganese, rhenium, iridium, lead, carbon, indium, gallium, iron, copper, tungsten, magnesium, niobium, nickel, tantalum, silicon, vanadium, gold, silver, palladium, platinum, cerium, zirconium, hafnium; carbides, nitrides, borides, hydrides, intermetallic compounds, oxides, or sulfides thereof; and combinations of the foregoing.
[0026] In some embodiments, the metal-containing functionalized material further comprises spherical metal or metal alloy powder.
[0027] The metal-containing functionalized material does not necessarily contain only non-spherical particles and microparticles. Other materials may be present. In certain embodiments, the combined concentration of non-spherical particles and microparticles is from 50vol% to 100vol% of the metal-containing functionalized material. The combined concentration of non-spherical particles and microparticles can be in various ranges, such as 50-60vol%, 60-74vol%, 75-85vol%, 85-95vol%, greater than 95vol%, greater than 99vol%, less than 50vol% or less than 100vol%. In certain embodiments, the combined concentration of non-spherical particles and microparticles is 100vol%, that is, the metal-containing functionalized material is composed of non-spherical particles and functionalized microparticles.
[0028] Some variations of the invention provide a method of making a metal-containing functionalized material, the method comprising:
[0029] (a) providing a bulk material containing a metal or a metal alloy;
[0030] (b) mechanically and / or chemically milling a bulk feedstock to produce a plurality of non-spherical particles comprising a metal or metal alloy, wherein the non-spherical particles are smaller than a length scale of the bulk feedstock;
[0031] (c) providing microparticles selected from the group consisting of metals, metal alloys, metal carbides, metal nitrides, metal borides, metal hydrides, metal oxides, metal sulfides, ceramics, and combinations thereof, wherein the microparticles are compositionally different from the non-spherical particles; and
[0032] (d) physically and / or chemically assembling microparticles onto the surface of the non-spherical particles, wherein the microparticles have an average particle size that is different from an average non-spherical particle size of the non-spherical particles.
[0033] In some method embodiments, mechanical milling and / or chemical milling does not substantially cause a solid-liquid phase transition of the metal or metal alloy. Mechanical milling and / or chemical milling can utilize mechanical milling selected from the group consisting of: ball milling, crushing, grinding, pulverizing, grinding, high shear mixing, vibration mixing, acoustic mixing, and combinations thereof. Alternatively or additionally, mechanical milling and / or chemical milling can utilize chemical milling selected from the group consisting of: etching, dealloying, acid treatment, alkali treatment, and combinations thereof.
[0034] In some embodiments, the bulk feedstock is in the form of a plate, sheet, ingot, extrudate, or a combination thereof. In some embodiments, the bulk feedstock comprises forgings, castings, semi-finished parts, machine shop prototypes, inferior parts, rejected parts, damaged parts, metal scraps, machining shavings, recycled parts, or a combination thereof.
[0035] In certain embodiments, non-spherical particles include whiskers, needle-shaped bodies, rods, fibers, oblate spheroids, prolate spheroids, parallelepipeds, rhombuses, rectangular prisms, flakes, polyhedral particles, particles of random shapes, or combinations thereof. The non-spherical particles can be characterized in that, for example, the median particle size (D50) is from 10 microns to 1 millimeter. The average particle size can be, for example, from 5 nanometers to 100 microns. Typically, the average particle size is less than the average non-spherical particle size, although this is not necessarily the case.
[0036] In some embodiments, the non-spherical particles contain a metal selected from the group consisting of aluminum, titanium, cobalt, chromium, iron, copper, tungsten, magnesium, niobium, nickel, tantalum, silicon, vanadium, gold, silver, cerium, molybdenum, zirconium, hafnium, and combinations thereof.
[0037] In some embodiments, the microparticles contain a metal selected from the group consisting of aluminum, titanium, cobalt, zinc, tin, chromium, iron, copper, tungsten, magnesium, niobium, nickel, tantalum, silicon, vanadium, gold, silver, palladium, platinum, cerium, zirconium, hafnium; carbides, nitrides, borides, hydrides, oxides, or sulfides thereof; and combinations of the foregoing. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 Non-spherical metal or metal alloy particles having flake geometry are depicted in exemplary embodiments.
[0039] Figure 2 Depicted is the assembly of surface functionalized microparticles on non-spherical particles in an exemplary embodiment.
[0040] Figure 3is a SEM image showing a single Al-7075 particle produced in Example 1 from mechanically milled extruded rod bulk starting material (scale bar = 1 mm).
[0041] Figure 4 The particle size distribution of the mechanically milled Al-7075 particles in Example 1 at different milling intensities is shown.
[0042] Figure 5 is a photograph showing a single Al-7075 particle produced by cryogenically milling the bulk starting material in Example 2 compared to a single Al-7075 particle produced by mechanically milling the bulk starting material at ambient temperature.
[0043] Fig. 6A is a SEM image showing a single Al-7075 non-spherical particle produced in Example 3 by mechanically grinding a bulk starting material followed by exposure to forming gas to form an embrittled material (scale bar = 200 microns).
[0044] Figure 6B Example 3 shows that further mechanical stirring Fig. 6A SEM image of a single Al-7075 non-spherical particle resulting from the embrittled material shown in (scale bar = 50 microns).
[0045] Fig. 7A is a SEM image of aluminum alloy particles functionalized with zirconium hydride (ZrH2) particles assembled on the surface of all Al-7075 non-spherical particles in Example 4 (scale bar = 400 microns).
[0046] Figure 7B is a SEM image of aluminum alloy particles functionalized with zirconium hydride (ZrH2) particles assembled on the surface of all Al-7075 non-spherical particles in Example 4 (scale bar = 300 microns).
[0047] Figure 8 is a photograph of a solidified metal alloy part formed by laser melting and solidification of ZrH2-functionalized Al-7075 non-spherical powder in Example 4 (scale bar = 3 mm).
[0048] Embodiments of the present invention
[0049] The compositions, structures, methods and systems of the present invention will now be described in detail with reference to various non-limiting examples.
[0050] This description will enable those skilled in the art to make and use the invention, and describes several embodiments, modifications, variations, alternatives and uses of the invention. These and other embodiments, features and advantages of the invention will become more apparent to those skilled in the art when reference is made to the following detailed description of the invention in conjunction with the accompanying drawings.
[0051] As used in this specification and the appended claims, the singular forms "a / an" and "the" include plural referents unless the context clearly dictates otherwise. Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.
[0052] Unless otherwise indicated, all numerical values expressing conditions, concentrations, dimensions, and the like used in the specification and claims are to be understood as being modified in all instances by the term "about." Accordingly, unless indicated to the contrary, the numerical parameters set forth in the following specification and appended claims are approximations that may vary at least as a function of the particular analytical technique.
[0053] The term "comprising," which is synonymous with "including," "containing," or "characterized by," is inclusive or open-ended and does not exclude additional, unrecited elements or method steps. "Comprising" is a specialized term used in claim language, meaning that the specified claim elements are essential, but other claim elements may be added and still constitute a concept within the scope of the claim.
[0054] As used herein, the phrase "consisting of excludes any elements, steps, or ingredients not specified in the claim. When the phrase "consisting of" (or variations thereof) appears in a clause in the body of a claim, rather than immediately following the preamble, the phrase is limited only to the elements set forth in that clause; other elements are not excluded from the claim as a whole. As used herein, the phrase "consisting essentially of limits the scope of a claim to the specified elements or method steps, plus those that do not materially affect the basis and novel feature or features of the claimed subject matter.
[0055] With respect to the terms "comprising," "consisting of," and "consisting essentially of," where one of these three terms is used herein, the presently disclosed and claimed subject matter may include the use of any of the other two terms, except when used with Markush groups. Thus, in some embodiments not otherwise explicitly recited, any instance of "comprising" may be replaced by "consisting of," or alternatively, "consisting essentially of."
[0056] Some variations of the present invention provide an alternative to the current trade-off between material cost and component performance in powder-based metal additive manufacturing and other powder metallurgy processes. Rather than using gas or water atomization of powder as the sole means of powder production, the methods disclosed herein employ mechanical stirring or chemical milling to produce non-spherical metal or metal alloy powders from wrought, non-weldable feedstocks that are incompatible with typical metal additive manufacturing processes. The surface of the non-spherical powder is then covered with a plurality of other smaller particles to control the solidification conditions of the non-spherical powder as it undergoes a phase transformation.
[0057] This discovery enables the use of ultra-low cost (<$45 / kg) feedstock materials, since wrought, non-weldable materials (e.g., 2000 or 7000 series aluminum alloys) are readily available in bulk form or as waste from other industrial processes (e.g., recycling, machining scrap, scrap parts, etc.). By incorporating surface assembled microparticles to functionalize metals or metal alloys and make them compatible with metal additive manufacturing and other powder metallurgy processes, new feedstocks that have heretofore been unavailable can be used.
[0058] Some variations of the present invention provide a means of forming high-performance, low-cost powders by avoiding conventional gas or water atomization processes. In some embodiments, a controlled atmosphere heat treatment is applied to change the morphology of the raw material, and then a mechanical stirring or chemical milling step is performed to produce particles (powders) from the raw material without undergoing a phase change that melts and resolidifies the particles in a gas or water flow. Multiple functional, smaller particles are then scalably assembled on the surface of the non-atomized powder particles to make the powder compatible with powder metallurgy or metal additive manufacturing processes. By combining a low-cost method for forming powders with a method for making metal alloys compatible with metal additive manufacturing processes, variations of the present invention solve the process cost and raw material availability issues in current metal additive manufacturing and powder metallurgy.
[0059] Conventional atomization processes for forming spherical, monodisperse powder feedstocks significantly increase costs (typically >20X) compared to the input ingot material used for atomization. Problems with conventional atomization include: (a) the large amount of time and energy required to melt and spray atomize large quantities of powder (thousands of kilograms); (b) safety issues with the formation of combustible dust clouds in powders less than 100 microns; (c) low yields (25%-35%) within the desired size range (15-60 microns); (d) the inability to remelt and reuse waste or unqualified powders; and (e) the lack of a secondary market for ingot materials with expensive alloying elements (e.g., Ag, Sc, or Ti) used to form powder feedstocks. In contrast, the present invention does not require expensive atomization and does not require ingot materials containing expensive alloying elements. In addition, reuse and recycling are important features in some variations of the present invention compared to conventional atomization processes.
[0060] Methods for recycling powder feedstock are known. See Asgari et al., "On microstructure and mechanical properties of additively manufactured AlSi10Mg_200C using recycled powder," Materials Science & Engineering A 707 (2017) 148-158; and Strondl et al., "Characterization and Control of Powder Properties for Additive Manufacturing," JOM, Vol. 67, No. 3, (2015) 549-554, which are hereby incorporated by reference. In these prior art methods, powder feedstock or parts produced from powder feedstock are processed to obtain a particle size distribution compatible with metal additive manufacturing. However, it is important to note that no additional processing or material is added to these materials. Prior to post-processing, these materials are already weldable or compatible with metal additive manufacturing processes. In contrast, in the present invention, the starting materials (prior to surface functionalization) do not need to be weldable or compatible with metal additive manufacturing.
[0061] As an example, according to the principles described herein, high performance wrought metal alloys (e.g., 2000 and 7000 series aluminum alloys) can be used in various manufacturing processes (e.g., metal additive manufacturing) without incurring the typical cost penalty (>20X compared to the price of the raw materials) resulting from gas or water atomization processes. Therefore, it is particularly advantageous to include a significant portion (e.g., 15 vol% or more) of the metal alloy component in a commercial product line. Good examples of these applications include, but are not limited to, commercial aviation and high performance automotive platforms for which metal additive manufacturing costs have heretofore been unable to compete with subtractive machining processes.
[0062] Metal-containing functionalized materials have a unique, observable physical structure for powder feedstocks used in metal additive manufacturing or other powder metallurgy processes. Compared to typical gas atomized powder feedstocks used in additive manufacturing processes, metal-containing functionalized materials contain non-spherical particles that can be formed from non-weldable wrought metal alloy feedstocks. The non-spherical particles are produced by mechanical stirring or chemical milling, where no phase change occurs, i.e., no melting and re-solidification occurs during the formation of the powder feedstock. For example, the absence of a solid-to-liquid phase transition of the metal or metal alloy can be detected in the final material using imaging analysis.
[0063] Some variations provide a metal-containing functionalized material comprising:
[0064] (a) a plurality of non-spherical particles comprising a metal or a metal alloy; and
[0065] (b) a plurality of microparticles physically and / or chemically assembled on the surface of the non-spherical particle, wherein the microparticles are selected from the group consisting of metals, metal alloys, metal carbides, metal nitrides, metal borides, metal hydrides, metal oxides, metal sulfides, ceramics, and combinations thereof,
[0066] wherein the microparticles are compositionally different from the non-spherical particles, and
[0067] The particles have an average particle size that is different from an average non-spherical particle size of the non-spherical particles.
[0068] In the present disclosure, "non-spherical" particles mean that the particles have a sphericity of less than 1.0. Sphericity is the ratio of the surface area of a sphere with the same volume as a given particle to the surface area of the particle. In some embodiments, non-spherical particles have a sphericity of about or less than about 0.99, 0.98, 0.97, 0.96, 0.95, 0.94, 0.93, 0.92, 0.91 or 0.90. The sphericity of a perfect sphere is exactly 1, which is the maximum value of sphericity. As other examples, the sphericity of a cube is 0.81, while the sphericity of a tetrahedron (triangular pyramid) is 0.67. The sphericity of a high aspect ratio shape (e.g., a rod) is much less than 1.
[0069] In some embodiments, the non-spherical particles are selected from whiskers, needles, rods, fibers, oblate spheroids, prolate spheroids, parallelepipeds, rhombuses, rectangular prisms, flakes, polyhedral particles, particles of random shapes, and / or combinations thereof. In typical embodiments, there are non-spherical particles of various shapes, which can lead to better packing efficiency.
[0070] Non-spherical particles can be characterized by particle size, which is also referred to as the characteristic dimension of the non-spherical particle. In some embodiments, the characteristic dimension is the effective diameter, i.e., the diameter of the particle calculated from an imaginary sphere of the same volume as the volume of the particle being analyzed. In some embodiments, the characteristic dimension is the particle length, which can be used, for example, for whiskers, needles, rods, and fibers. In some embodiments, the characteristic dimension is the maximum width of the flake (in a dimension transverse to the thickness), such as Figure 1 shown.
[0071] Particle size can be measured by a variety of techniques, including, for example, dynamic light scattering, laser diffraction, image analysis, or sieve separation. Dynamic light scattering is a non-invasive established technique for measuring the size and size distribution of particles typically in the submicron region (and the latest technology is even 1 nanometer). Laser diffraction is a widely used particle measurement technique for materials ranging in size from hundreds of nanometers to several millimeters. Exemplary dynamic light scattering instruments and laser diffraction instruments for measuring particle size can be obtained from Malvern Instruments Ltd., Worcestershire, UK. Image analysis can be performed directly on micrographs, scanning electron micrographs or other images to estimate particle size and distribution. Finally, sieving is a conventional technique for separating particles by size.
[0072] In certain embodiments utilizing laser diffraction, particle size is calculated by measuring the angle of light scattered by a particle as it passes through a laser beam. Laser diffraction measures particle size distribution by measuring the angular change in the intensity of scattered light as a laser beam passes through a dispersed sample of particles. Particle size is reported as a volume equivalent spherical diameter. The D10, D50, and D90 values and ranges disclosed herein are mass values (rather than number or volume values).
[0073] The non-spherical particles can be characterized by a median particle size (D50) of from 5 microns to 10 millimeters. D50 represents the particle size corresponding to 50% (by mass) cumulative undersize particle size distribution. For example, for a D50 value of 25 microns, 50% of the non-spherical particles are less than 25 microns. In various embodiments, the median particle size is, for example, in the range of 15-45 μm, 40-70 μm, 45-70 μm, 70-125 μm, 125-300 μm, 300-600 μm or 600-10000 μm. In some embodiments, the D50 particle size is less than 1000 μm (1 millimeter).
[0074] The non-spherical particles can be characterized by a D10 particle size of from 0.1 microns to 1 mm. D10 represents the particle size corresponding to the 10% (by mass) cumulative undersize particle size distribution. For example, for a D10 value of 5 microns, 10% of the non-spherical particles are less than 5 microns. In some embodiments, the D10 particle size is less than 0.1 microns.
[0075] The non-spherical particles can be characterized by a D90 particle size of from 20 microns to 100 mm. D90 represents the particle size corresponding to the 90% (by mass) cumulative undersize particle size distribution. For example, for a D90 value of 50 microns, 90% of the non-spherical particles are less than 50 microns. In some embodiments, the D90 particle size is less than 20 microns.
[0076] The particle size distribution of non-spherical particles can be monodisperse or polydisperse. In addition, the particle size distribution of non-spherical particles can be unimodal or multimodal, such as bimodal. In certain embodiments, the particle size distribution is bimodal, which results in good packing efficiency of the particles.
[0077] The "packing efficiency" of a particle is the density of the particles when they are actually packed divided by the density of the particle material itself. Thus, a single thick sheet of non-porous material has a packing efficiency of 100%. A perfect sphere has a packing efficiency of about 74%. In some embodiments of metal-containing functionalized materials, non-spherical particles are characterized by a packing efficiency of from 40% to 65%, such as 40%-49%, 49%-55%, 55%-60%, or 60%-65%. In certain embodiments of the present invention, the packing efficiency is less than 64%. In the case of certain random shapes, the packing efficiency is less than 40%. In certain embodiments, a combination of shape and size results in a packing efficiency greater than 65%.
[0078] It should be noted that the metal-containing functionalized material may further comprise spherical particles containing metal or metal alloy. Spherical or nearly spherical particles may exist as impurities or as particles of random shapes that are arbitrarily close to a spherical shape.
[0079] In certain embodiments, a certain amount of spherical or nearly spherical particles (e.g., purchased spherical particles) containing metals or metal alloys can be intentionally added to the metal-containing functionalized material, or the metal-containing functionalized material can be added to the spherical particles. Among the particles containing base metals or metal alloys (i.e., the above-mentioned element (a), excluding microparticles), preferably less than 10%, and more preferably less than 5%, less than 2%, less than 1%, less than 0.5%, less than 0.2%, less than 0.1%, less than 0.05%, less than 0.02% or less than 0.01% are spherical (these percentages are based on the number of particles containing base metals or metal alloys). In some embodiments, there are substantially no detectable spherical particles in the base metal or metal alloy.
[0080] In some embodiments, the non-spherical particles contain a metal selected from the group consisting of aluminum, titanium, cobalt, chromium, iron, copper, tungsten, magnesium, niobium, nickel, tantalum, silicon, vanadium, gold, silver, platinum, palladium, iridium, rhenium, zinc, cerium, molybdenum, zirconium, hafnium, and alloys or combinations thereof. The non-spherical particles may contain at least 50 vol%, at least 60 vol%, at least 70 vol%, at least 80 vol%, at least 90 vol%, at least 95 vol%, at least 99 vol%, or 100 vol% of one or more of these metals. For example, when the non-spherical particles contain a metal alloy, the metal alloy may contain an intermetallic phase, a ceramic phase, or a phase including one or more p-zone elements (e.g., C, N, O, etc.).
[0081] For the purposes of this disclosure, metalloids such as silicon are considered metals.
[0082] In the present disclosure, a "particle" can be a nanoparticle, a microparticle, an agglomerate, an inclusion, or a reaction product. The particle can be of any shape, including spherical or non-spherical. In some embodiments, the particle is selected from spheres, whiskers, needles, rods, fibers, oblate spheroids, prolate spheroids, parallelepipeds, rhombuses, rectangular prisms, flakes, polyhedral particles, randomly shaped particles, and / or combinations thereof. As an example, Figure 1 Non-spherical metal or metal alloy particles having a flake geometry are depicted. The particles may also be referred to as "functionalizing particulates, functionalization particulates," "surface functionalized particulates," and the like.
[0083] The average particle size can be, for example, from 5 nanometers to 100 microns. Typically, the average particle size is smaller than the average non-spherical particle size. In some embodiments, the average particle size is at least one order of magnitude smaller than the average non-spherical particle size. In other embodiments, the average particle size is equal to or greater than the average non-spherical particle size.
[0084] In various embodiments, the average (D50) particle size is about, at least about, or at most about 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, or 100 μm.
[0085] The number of particles per particle may vary widely. The average number of individual particles disposed on a particle (equivalently, the average number ratio of particles to particles) may be, for example, about 10, about 10, or about 10. 2 , about 10 3 , about 10 4 , about 10 5 , or about 10 6 The distribution of particles on the surface of the particle can vary. In some embodiments, certain surface areas contain relatively high concentrations of particles, and the particles may agglomerate on the surface of those areas.
[0086] In various embodiments, the particle surface coverage can also vary widely from about 1% to 100%. The particle surface coverage is the average area fraction of the particle covered by the assembled particles. For example, the particle surface coverage can be about, or at least about 1%, 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, or 100%. Due to the generally small size of the particles, it may be advantageous to have a surface area coverage of less than 1%.
[0087] In some embodiments, microparticles form a continuous coating on non-spherical particles. In other embodiments, microparticles form a discontinuous coating on non-spherical particles. When microparticles form a discontinuous coating, the surface coverage may vary widely. Typically, microparticles can be present on non-spherical particles with an average surface coverage of about 0.1% to about 100%. Some non-spherical particles can have a surface coverage of 100%, forming a continuous coating on these particles, while other non-spherical particles can have a surface coverage of less than 100%, usually forming a discontinuous coating. (Continuous coatings with surface coverages lower than 100% are possible, such as elongated islands interconnected on the surface.) Although not desirable, there may be some non-spherical particles that have no microparticles at all on the coating, while other non-spherical particles are coated with microparticles. Finally, some or all of the non-spherical particles can be coated with multiple layers of microparticles in a continuous or discontinuous manner.
[0088] In some embodiments, the microparticles contain a metal selected from the group consisting of aluminum, titanium, cobalt, zinc, tin, chromium, bismuth, neodymium, dysprosium, erbium, samarium, praseodymium, gadolinium, ytterbium, lanthanum, boron, lithium, calcium, strontium, scandium, yttrium, manganese, rhenium, iridium, lead, carbon, indium, gallium, iron, copper, tungsten, magnesium, niobium, nickel, tantalum, silicon, vanadium, gold, silver, palladium, platinum, cerium, zirconium, hafnium; carbides, nitrides, borides, hydrides, intermetallic compounds, oxides, or sulfides thereof; and combinations of the foregoing.
[0089] In some embodiments, the particles contain a material selected from the group consisting of SiC, HfC, TaC, ZrC, NbC, WC, TiC, TiC 0.7 N 0.3, VC, B4C, TiB2, HfB2, TaB2, ZrB2, WB2, NbB2, TaN, HfN, BN, ZrN, TiN, NbN, VN, Si3N4, Al2O3, MgAl2O3, HfO2, ZrO2, Ta2O5, TiO2, SiO2, oxides of rare earth elements Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and / or Lu, and ceramic materials of the group consisting of combinations of the foregoing substances.
[0090] In other embodiments, the particles comprise carbonaceous materials such as graphite, graphene, carbon black, carbon fibers, carbon polymer composites, activated carbon, carbon nanostructures (eg, carbon nanotubes), diamonds (eg, nanodiamonds), and combinations thereof.
[0091] In general, the particles and / or microparticles may contain one or more elements selected from the group consisting of Al, Si, Fe, Cu, Ni, Mn, Mg, Cr, Zn, V, Ti, Bi, Ga, Pb, Zr, H, Li, Be, B, C, N, O, F, Na, P, S, Cl, K, Ca, Sc, Co, Zn, Ga, Ge, As, Se, Br, Rb, Sr, Y, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Cd, In, Sn, Te, I, Cs, Ba, Hf, Ta, W, Re, Os, Ir, Pt, Au, Hg, Tl, Ce, Nd, and combinations thereof. In addition to the particles and microparticles, additional elements may also be present in the overall composition. For example, P-block elements and / or F-block elements may be incorporated into particles, microparticles, both particles and microparticles, or may be neither in particles nor microparticles, but as unique additives in the metal-containing functionalized material.
[0092] As a specific example involving zirconium, the zirconium-containing particles may be ZrH x (x=0 to 4) (ie, in the form of a hydride when x>0). An exemplary zirconium hydride is zirconium dihydride, ZrH2. As another specific example involving zirconium, the zirconium-containing particulate may be present as zirconium aluminide Al3Zr.
[0093] In some embodiments, the particles include an intermetallic compound selected from the group consisting of Al3Zr, Al3Ta, Al3Nb, Al3Ti, TiB, TiB2, WC, AlB, and combinations thereof.
[0094] The volume loading of microparticles on non-spherical particles can vary widely, based on the total volume of non-spherical particles plus microparticles physically and / or chemically assembled on the surface of non-spherical particles, such as about 0.01 vol% to about 20 vol%. In some preferred embodiments, the volume loading of microparticles on non-spherical particles is about 0.5 vol% to about 3 vol%. In various embodiments, the volume loading of microparticles on non-spherical particles is about, or at least about, or at most about 0.01, 0.05, 0.1, 0.2, 0.5, 1, 1.5, 2, 2.5, 3, 4, 5, 6, 7, 8, 9, 10, 15, or 20 vol%.
[0095] In some embodiments, the combined concentration of non-spherical particles and microparticles is from 50 vol% to 100 vol% of the functionalized material containing metal. The combined concentration of non-spherical particles and microparticles can be in various ranges, such as 50-60 vol%, 60-74 vol%, 75-85 vol%, 85-95 vol%, greater than 95 vol%, greater than 99 vol%, less than 50 vol%, or less than 100 vol%. In certain embodiments, the combined concentration of non-spherical particles and microparticles is 100 vol%.
[0096] In certain embodiments, the metal-containing functionalized material further comprises spherical metal or metal alloy powder.Spherical metal or metal alloy powder can be derived from gas or water atomization.The metal or metal alloy in the spherical powder can be the same or different from the metal or metal alloy in the non-spherical particles.In addition, the metal or metal alloy in the spherical powder may or may not be physically and / or chemically assembled on the surface of the spherical particles.When the spherical particles (if present) have particles physically and / or chemically assembled on the surface, these particles can be independently selected from the group consisting of metal, metal alloy, metal carbide, metal nitride, metal boride, metal hydride, metal oxide, metal sulfide, ceramic and combinations thereof (with the particles on the non-spherical particles).When the metal-containing functionalized material contains spherical metal or metal alloy powder, its concentration (in the total metal-containing functionalized material) can be less than 20wt%, less than 10wt%, less than 5wt%, less than 2wt%, less than 1wt%, less than 0.5wt%, less than 0.2wt% or less than 0.1wt%.
[0097] Methods for making and using metal-containing functionalized materials will now be described. In various embodiments, the method objectives may include forming a powder from a larger bulk solid; assembling a plurality of particles on the surface of the particles to form a functionalized powder; and / or melting and solidifying the functionalized powder in response to the application of an energy source (e.g., a laser beam or an electron beam).
[0098] As described above, a non-spherical particle powder comprising a metal or metal alloy is produced from a bulk starting material. The characteristic size of the bulk starting material is greater than the characteristic size of the powder. For example, the characteristic size of the bulk starting material can be on the order of 1 mm, 1 cm, 10 cm, or 1 m. The characteristic size of the powder is less than the characteristic size of the bulk starting material. For example, the characteristic size of the powder can be on the order of 1 mm, 100 microns, 10 microns, or 1 micron.
[0099] In the present invention, many sources of bulk starting material are possible. Exemplary sources include, but are not limited to, original, unprocessed metal forms, such as extrudates, ingots, plates, sheets, etc.; semi-finished metal forms, such as forgings, castings, or machined parts; finished or semi-finished components, such as parts or prototypes; recycled or regenerated materials, such as machining scrap, used parts, inferior parts, damaged parts, scrap parts, metal scraps, machining shavings, recycled parts, or recycled metals; or combinations thereof. In certain embodiments, the bulk starting material is a sieved powder from a gas atomization process that produces small particles with oversized particles that form the bulk starting material.
[0100] Importantly, the bulk starting material need not be a material that is compatible with additive manufacturing or other powder metallurgy processes, even if it is ultimately desired to use the metal-containing functionalized material in an additive manufacturing or other powder metallurgy process. The reason is that the surface-assembled particles are used to control the processing and properties of the powder formed from the bulk starting material. In preferred embodiments, the metal-containing functionalized material is suitable for additive manufacturing and / or other powder metallurgy processes.
[0101] The process of reducing the size of the bulk starting material into non-spherical metal or metal alloy particles may include mechanical agitation, chemical milling, or both mechanical agitation and chemical milling.
[0102] When mechanical agitation is employed, exemplary methods include, but are not limited to, milling, ball milling, crushing, grinding, pulverizing, grinding, machining, jet milling, high shear mixing, vibration mixing, or acoustic mixing. In some embodiments, strain energy is also applied to the bulk starting material, such as by shear forces. An exemplary apparatus for mechanical agitation is a planetary ball mill.
[0103] For example, mechanical milling can be performed at or near ambient temperature (e.g., about 25°C) or at elevated temperatures, such as about 0°C, 25°C, 50°C, 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, or 600°C. In some embodiments, mechanical milling is performed at low temperatures to promote ductile-brittle transitions, such as temperatures from about -270°C to about 0°C, such as about -250°C, -200°C, -150°C, -100°C, -75°C, -50°C, or -25°C (e.g., in cryogenic milling). The mechanical milling temperature is preferably selected or adjusted (e.g., by cooling) so that the bulk starting material or non-spherical metal or metal alloy particles do not undergo substantial solid-liquid phase transitions. Mechanical milling can be performed, for example, for a milling time of about, at least about, or at most about 10 minutes, 30 minutes, 1 hour, 2 hours, 4 hours, 8 hours, 12 hours, 24 hours, or 48 hours.
[0104] When chemical milling is employed, exemplary methods include, but are not limited to, etching, acid treatment, base treatment, dealloying, or photochemical milling.Chemical milling can be used to reduce the size of the bulk starting material without or in combination with mechanical agitation.
[0105] For example, chemical milling can be performed at or near ambient temperature (e.g., about 25°C) or at elevated temperatures, such as about 0°C, 25°C, 50°C, 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, or 600°C. The chemical milling temperature is preferably selected or adjusted (e.g., by cooling) so that substantially no solid-to-liquid phase transition occurs (of the bulk starting material or the non-spherical metal or metal alloy particles). Chemical milling can utilize a bias charge to facilitate controlled milling. Chemical milling can be performed, for example, for a milling time of about, at least about, or at most about 10 minutes, 30 minutes, 1 hour, 2 hours, 4 hours, 8 hours, 12 hours, 24 hours, or 48 hours.
[0106] In a preferred method embodiment, mechanical milling and / or chemical milling does not substantially induce a solid-liquid phase transition of the metal or metal alloy. "Substantially no solid-liquid phase transition" means that the milling process does not require a solid-liquid phase transition to reduce the particle size, and the average temperature of the milling process is below the melting temperature of all metals present in a concentration greater than 1 wt %, or, in the case of a eutectic metal alloy, below the eutectic temperature of the metal alloy.
[0107] In some embodiments involving metal alloys, mechanical milling is performed below the liquidus temperature of the metal alloy, and preferably below the solidus temperature of the metal alloy. In some embodiments involving metal alloys, chemical milling is performed below the liquidus temperature of the metal alloy, and optionally below the solidus temperature of the metal alloy.
[0108] When high energy mechanical agitation is used for milling, local hot spots may form, such as at the interface between the metal feedstock and the mixing ball. The temperature of the local hot spot may exceed the melting temperature of one or more metals present in the feedstock, and in the case of a eutectic metal alloy, may exceed its eutectic temperature. In this case, a small amount of spherical particles may be produced, such as less than 10 wt%, less than 5 wt%, less than 2 wt%, less than 1 wt%, less than 0.5 wt%, less than 0.2 wt%, less than 0.1 wt%, less than 0.05 wt%, less than 0.02 wt%, or less than 0.01 wt% of the total mass of the particles. Because the solid-liquid phase transition caused by these hot spots is only accidental, such melting is considered to be essentially free of solid-liquid phase transition during the milling process.
[0109] In contrast, in gas atomization for metal powder production, the elemental feedstock is melted under a blanket of air or inert gas or under vacuum. The chamber is backfilled with gas to force the molten metal through a nozzle, where the high-velocity gas impinges on the flowing melt and breaks it into droplets that are spherical due to minimized surface tension. The droplets then resolidify, forming spherical particles. In this particle-forming technique, the metal undergoes a solid-to-liquid phase transition. Other techniques for hot assembly into spherical particles include water atomization, plasma atomization, centrifugal atomization, electrode-induced melting gas atomization, plasma rotating electrode process, and plasma spheroidization, all of which require a solid-to-liquid phase transition as opposed to mechanical stirring and / or chemical milling, which do not.
[0110] In some embodiments, the bulk starting material can be pretreated and / or co-treated (along with milling) to reduce its ductility. Metal ductility is a measure of the ability of a metal to withstand significant plastic deformation before fracture. When mechanically milling the bulk starting material, it needs to be broken. Therefore, the reduction in ductility is conducive to making the bulk starting material easier to produce particles of the desired size range with lower energy requirements. When a pretreatment or co-treatment to reduce ductility is used, it can be carried out in the gas phase and / or the liquid phase.
[0111] Examples of pretreatments or concurrent treatments that reduce ductility may include, but are not limited to, exposing the bulk starting material to elevated temperatures in a vacuum or in the presence of air, an inert gas, or a forming gas (e.g., H2, CO, etc.) to embrittle the metal or metal alloy. For example, embrittlement may be caused by intergranular embrittlement, hydrogen embrittlement, formation of brittle intermetallic phases or particles, etching, chemical milling, chemical attack in intergranular regions, selective dealloying, or a combination thereof.
[0112] For example, the pretreatment or simultaneous treatment to reduce ductility can be performed at ambient temperature (e.g., about 25°C) or at an elevated temperature, such as about 50°C, 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, or 600°C. The pretreatment or simultaneous treatment to reduce ductility can be performed, for example, for a treatment time of about, at least about, or at most about 10 minutes, 30 minutes, 1 hour, 2 hours, 4 hours, 8 hours, 12 hours, or 24 hours. When desired, the elevated temperature can reduce the time required to embrittle the metal or metal alloy feedstock. The pretreatment or simultaneous treatment to reduce ductility can be performed in the presence of hydrogen or a hydrogen-containing gas (e.g., syngas) to induce hydrogen embrittlement.
[0113] In some embodiments employing mechanical agitation and a process that simultaneously reduces ductility, milling can be performed at low temperatures (cryo-milling) to reduce the size of the particles. In some embodiments employing chemical milling and a process that simultaneously reduces ductility, chemical milling can be performed at low temperatures to reduce the size of the particles.
[0114] Optionally, a passivating medium such as a milling medium or a grinding medium may be introduced into the mechanical stirring process to control particle size distribution, improve yield, and reduce the time required for mechanical stirring. Exemplary media include, but are not limited to, steel (e.g., carbon steel, chrome steel, or stainless steel) and ceramics (e.g., agate, alumina, yttria-stabilized zirconium oxide, zirconium silicate, zirconium oxide-toughened alumina, or tungsten carbide). Optionally, a chemical additive (e.g., stearic acid) may also be applied to lubricate the surface of the powder particles, prevent particle agglomeration, or reduce contamination from the passivating medium.
[0115] After forming a plurality of non-spherical particles within the above-mentioned size range, a plurality of fine particles having a composition and a size different from those of the non-spherical particles are assembled on the surface of the particles. Figure 2 The assembly of surface functionalized microparticles on non-spherical particles is depicted. The surface functionalized microparticles functionalize the surface of the non-spherical particles, demonstrating a metal-containing functionalized material. Functionalization can adjust or control the composition, microstructure and / or processability of the metal-containing functionalized material that can be used in additive manufacturing or other powder metallurgy processes.
[0116] For example, microparticles can allow controlled solidification after a phase transformation of a non-spherical particle. Microparticles can allow control of grain size and / or grain quality in a solidified metal-containing functionalized material. Microparticles can allow strengthening of metal alloys. Microparticles can allow the formation of metal matrix composites. Microparticles can allow microalloying of non-spherical particles or the formation of compositions that would not otherwise be obtained by gas atomization. For example, compositions that would otherwise be unobtainable could include insoluble additives; compositions that would evaporate if left in the liquid phase for a long time during melt atomization; or compositions that would form or coarsen brittle intermetallic phases.
[0117] Various types of materials can be used for functionalized particles. Examples include pure metals, metal alloys, metal carbides, metal oxides, metal nitrides, metal hydrides, metal borides and combinations thereof. Alternatively or additionally, oxide or non-oxide ceramic particles can be used. Preferably, a single composition of functionalized particles is used, although a variety of different functionalized particle compositions can be used. In some embodiments, functionalized particles are added to all non-spherical particles. In other embodiments, functionalized particles are assembled onto a subset of non-spherical particles.
[0118] The surface functionalized microparticles can be obtained from any source, such as a commercial manufacturer. In some embodiments, the surface functionalized microparticles can be produced by mechanical milling, chemical milling, gas atomization, or liquid atomization of a starting material. The starting material can be purchased raw material to be milled in the form of pellets, ingots, plates, sheets, etc. The starting material for making the microparticles can include semi-finished metal forms, such as forgings, castings, or machined parts; finished or semi-finished parts, such as parts or prototypes; recycled or regenerated materials, such as machining waste, used parts, inferior parts, damaged parts, scrap parts, metal waste, machining chips, recycled parts, or recycled metals; or combinations thereof.
[0119] Some variations of the invention provide a method of making a metal-containing functionalized material, the method comprising:
[0120] (a) providing a bulk material containing a metal or a metal alloy;
[0121] (b) mechanically and / or chemically milling a bulk feedstock to produce a plurality of non-spherical particles comprising a metal or metal alloy, wherein the non-spherical particles are smaller than a length scale of the bulk feedstock;
[0122] (c) providing microparticles selected from the group consisting of metals, metal alloys, metal carbides, metal nitrides, metal borides, metal hydrides, metal oxides, metal sulfides, ceramics, and combinations thereof, wherein the microparticles are compositionally different from the non-spherical particles; and
[0123] (d) physically and / or chemically assembling microparticles onto the surface of the non-spherical particles, wherein the microparticles have an average particle size that is different from an average non-spherical particle size of the non-spherical particles.
[0124] In some method embodiments, non-spherical particles include whiskers, needles, rods, fibers, oblate spheroids, prolate spheroids, parallelepipeds, rhombuses, rectangular prisms, flakes, polyhedral particles, and particles of random shapes. The non-spherical particles can be characterized by, for example, a median particle size (D50) of from 10 microns to 1 millimeter. The average particle size can be, for example, from 5 nanometers to 100 microns. Typically, the average particle size is less than the average non-spherical particle size, although this is not necessarily the case.
[0125] In some embodiments, the non-spherical particles contain a metal selected from the group consisting of aluminum, titanium, cobalt, chromium, iron, copper, tungsten, magnesium, niobium, nickel, tantalum, silicon, vanadium, gold, silver, cerium, molybdenum, zirconium, hafnium, and combinations thereof.
[0126] In some embodiments, the microparticles contain a metal selected from the group consisting of aluminum, titanium, cobalt, zinc, tin, chromium, iron, copper, tungsten, magnesium, niobium, nickel, tantalum, silicon, vanadium, gold, silver, palladium, platinum, cerium, zirconium, hafnium; carbides, nitrides, borides, hydrides, oxides, or sulfides thereof; and combinations of the foregoing.
[0127] Microparticles can be attached to non-spherical particles using electrostatic forces, van der Waals forces, chemical bonds, physical bonds, and / or any other forces. Chemical bonds are forces that hold atoms together in a molecule or compound. Electrostatic forces and van der Waals forces are examples of physical forces that can cause bonding. Physical bonding is bonding that occurs when molecular entities become entangled in space. Typically, chemical bonds are stronger than physical bonds. Chemical bonds can include ionic bonds, covalent bonds, or combinations thereof.
[0128] Many methods can be used to attach microparticles to non-spherical particles. Some methods include immersion deposition, electroless deposition, vapor coating, solution / suspension coating of particles with or without organic ligands, and attachment of particles using electrostatic and / or van der Waals forces through mixing.
[0129] In some variations, a solvent method is used, in which a solvent (such as water or tetrahydrofuran) and microparticles are added to a powder of non-spherical particles, mixed, and then dried. The selection of one or more solvents will depend on the solvent compatibility of the microparticles and the non-spherical particles. The solvent should dissolve or suspend at least one component (microparticles or non-spherical particles). In certain embodiments, a slurry of dispersed microparticles in a solvent is sprayed on the powdered raw material and mixed simultaneously to coat all non-spherical particles with microparticles. After removing the solvent, van der Waals forces, chemical bonds, physical adsorption, or other forces can cause the microparticles to remain on the surface of the non-spherical particles.
[0130] The microparticles may be dissolved in a solvent having a lower surface energy than the microparticles. In some embodiments, when the solvent evaporates from the mixture of microparticles and non-spherical particles, the microparticles are pulled to the surface of the non-spherical particles by capillary forces.
[0131] The solvent used to dissolve or suspend the microparticles and / or non-spherical particles can be selected from polar organic solvents (e.g., acetone), non-polar organic solvents (e.g., n-hexane), polar inorganic solvents (e.g., water), non-polar inorganic solvents, ionic liquids, compressed and liquefied gases (e.g., liquefied carbon dioxide), supercritical fluids (e.g., supercritical carbon dioxide), or combinations thereof.
[0132] In certain embodiments, the solvent comprises or is substantially composed of compressed and liquefied gas and / or supercritical fluid. In certain embodiments, the solvent is liquefied or supercritical CO . Adopting liquefied or supercritical CO solution of particulate and non-spherical particles allows mixing non-spherical particles in a fluidized bed, has the benefit of not needing flammable solvents (that is, mixing under the atmosphere that can not ignite). After surface functionalization, CO can be discharged rapidly and reused, thereby eliminating waste and also drying powder simultaneously. After removing liquefied or supercritical CO , van der Waals force, chemical bond, physical adsorption or other forces can cause particulate to be retained on the surface of non-spherical particles.
[0133] In some variations, microparticles are assembled onto non-spherical particles by dry mixing, wherein the microparticles are added to a dry powder feedstock and mixed. Dry mixing can be accomplished by stirring, rolling, vibration, ball milling, centrifugation, fluidized bed blending, ultrasonic treatment or other mechanical techniques. Dry mixing can be performed with a gaseous mixing medium, such as, but not limited to, air, nitrogen, carbon dioxide, argon or a combination thereof. After dry mixing, van der Waals forces, chemical bonds, physical adsorption or other forces can cause the microparticles to remain on the surface of the non-spherical particles.
[0134] Some embodiments employ sonication. Sonication is the application of acoustic energy (eg, at a frequency of 20 kHz or higher) to agitate microparticles and non-spherical particles to promote mixing and assembly.
[0135] When dry mixing is performed using a gas phase mixing medium, it is preferred to maintain an atmosphere to keep the mixing medium, non-spherical particles and microparticles in a desired state. In addition, a closed environment is preferred to prevent particles from escaping from the system.
[0136] In some variations, microparticles are assembled onto non-spherical particles by electrostatic interactions. Electrostatic assembly can be performed by introducing opposite charges or at least polarity into microparticles and powder particle surfaces before or during surface functionalization. Electrostatic interactions are generally isotropic and quite strong, so they can be preferred. Electrostatic assembly can be completed by wet mixing (i.e., there is a solvent), dry mixing, or a combination of its order. For example, powder particles can be blown in as a dry material while mixing with microparticles, thereby causing the electrostatic charge that enables microparticles to be retained on the surface of powder particles. In these variations, electrostatic forces cause microparticles to be retained on the surface of powder particles. Charged microparticles (induced by air blowing as a dry material) can be deposited on the surface of non-spherical particles with opposite charges, while forming chemical bonds. Charge can also be induced by, for example, being exposed to an electric field or an electromagnetic field or by a chemical reaction.
[0137] Other techniques for assembling microparticles onto non-spherical particles include, but are not limited to, centrifugal sedimentation, electromagnetic sedimentation, electrochemical deposition, and pulsed laser deposition. Various force fields, such as electric, magnetic, or physical force fields, can be utilized. Physical forces can include, for example, high-speed impact, viscous flow, or large-amplitude oscillatory shear.
[0138] A particle-based coating may or may not be in the form of distinct, observable particles. That is, the coating may be derived from particles, but discrete particles are not necessarily present.
[0139] Assembly aids can be used in any of these assembly methods. Assembly aids enhance the retention of microparticles on the surface of powder particles. In particular, assembly aids can, for example, enhance the chemical kinetics of microparticle assembly, the thermodynamics of microparticle assembly, or the diffusion or mass transfer of microparticle assembly. Assembly aids can be selected from the group consisting of: surfactants, salts, dissolved ions, charged molecules, polar or non-polar solvents, microparticles of graded sizes, surface etchants for surface texture, and combinations thereof. For example, surfactants can reduce the surface tension between microparticles and the powder surface, thereby resulting in better wetting and assembly. Salts or ions can change the surface charge of microparticles or powder surfaces, thereby resulting in enhanced ionic bonds for assembly. Surface etchants can physically etch the surface of the powder to promote adsorption of microparticles.
[0140] When high surface coverage of microparticles on non-spherical particles is desired, drop casting, spin or spray coating, or Langmuir-Blodgett coating may be utilized.
[0141] In drop casting, the microparticle dispersion is spread on a substrate and dried under controlled conditions, such as pressure and temperature. In principle, the film thickness depends on the volume and particle concentration of the dispersion used, both of which can be easily changed. There are also other variables that affect the film structure, such as the degree of solvent wetting the substrate, evaporation rate, capillary forces associated with drying, etc. Usually, it is desirable to use a solvent that is volatile, wets the substrate and is not susceptible to film instability (dewetting). Due to low vapor pressure and large surface tension, water is often a poor solvent for drop casting. Organic solvents (such as hexane, toluene, alcohol or halogenated solvents) are usually good choices for microparticles with hydrophobic end-capping ligands.
[0142] Compared to drop casting, spin coating generally provides more uniform film thickness across the substrate and can accommodate larger substrates. In this technique, the substrate is spun at high speed and a volume of material with a known particle concentration is introduced into the center. Centrifugal forces spread the dispersion evenly across the substrate and then evaporate the solvent to produce a thin film of particles. Film thickness depends on the dispersion concentration, volume, and spin speed. As with drop casting, solvents other than water are advantageous. Slow removal of the substrate from the particle dispersion causes the particles to be drawn into the meniscus and deposited as the thin liquid layer dries.
[0143] Spraying utilizes a uniform atomized flow applied to the target substrate. For example, a syringe pump can be used to supply a constant liquid flow to a sprayer, in which the flow is mixed with an inert gas. The resulting mixture forms atomized droplets (containing microparticles), which are deposited on the substrate (non-spherical particles) in a uniform manner. The sprayer can be attached to a movable platform covering a wide range of areas. Volatile solvents are preferably used to maximize liquid evaporation and reduce any potential nanoparticle aggregation associated with capillary forces during the drying process.
[0144] The Langmuir-Blodgett trough provides a high level of control over the particle deposition process because the formation of the particle film can be separated from the transfer of the film to the substrate (non-spherical particles). When using this technique, the particle dispersion is evaporated on an immiscible liquid substrate in the Langmuir-Blodgett trough. A movable barrier can then be used to compress the particle layer to obtain a uniform monolayer or sub-monolayer film over a relatively large area. The substrate can be immersed in the particle layer, or the pre-immersed substrate can be removed, and the particle film is deposited at the liquid-solid interface. This technique is conducive to forming a uniform film over the entire non-spherical particle.
[0145] In some preferred embodiments, the metal-containing functionalized material is used in a powder-based metal additive manufacturing process, which includes applying a laser or electron beam energy source for melting and solidification. Alternatively or additionally, the metal-containing functionalized material can be used in other powder metallurgy processes, such as but not limited to sintering, field-assisted sintering, powder compaction, pressing, impact consolidation or extrusion. The metal-containing functionalized material can be used alone, i.e., accounting for 100% of the mass of the powder used for additive manufacturing or powder metallurgy. The metal-containing functionalized material can be used in combination with particles formed by another method (e.g., gas atomization).
[0146] In some preferred embodiments, the metal-containing functionalized material is a low-cost, high-strength metal alloy additive manufacturing powder feedstock formed from recycled or regenerated bulk wrought alloys.
[0147] Some variations provide a method for additively manufacturing a functionalized metal alloy, the method comprising:
[0148] (a) providing a metal-containing functionalized material;
[0149] (b) exposing the first amount of metal-containing functionalized material to an energy source to melt the first amount of metal-containing functionalized material to produce a first melt layer;
[0150] (c) solidifying the first molten layer to produce a first solid layer;
[0151] (d) repeating steps (b) and (c) a plurality of times to produce a plurality of solid layers by sequentially solidifying a plurality of melt layers in an additive manufacturing build direction, thereby producing an additively manufactured functionalized metal alloy; and
[0152] (e) Recycling of functionalized metal alloys produced by additive manufacturing,
[0153] The additively manufactured functionalized metal alloy preferably has a microstructure with equiaxed grains.
[0154] The energy source in step (b) can be provided by a laser beam, an electron beam, alternating current, direct current, plasma energy, induction heating from an applied magnetic field, ultrasonic energy, other sources, or a combination thereof. Typically, the energy source is a laser beam or an electron beam.
[0155] Method steps (b) and (c) can utilize a technology selected from, for example, the group consisting of: selective laser melting, electron beam melting, laser engineered net shaping, selective laser sintering, direct metal laser sintering, laser melting integrated with machining, laser powder injection, laser consolidation, direct metal deposition, wire directed energy deposition, plasma arc-based manufacturing, ultrasonic consolidation, and combinations thereof.
[0156] In certain embodiments, the additive manufacturing method is selected from the group consisting of selective laser melting, energy beam melting, laser engineered net shaping, and combinations thereof.
[0157] Selective laser melting uses a laser (e.g., a Yb fiber laser) to provide melting energy. Selective laser melting is designed to melt metal powders and fuse them together using a high power density laser. The process is capable of completely melting metal materials into solid 3D parts. A combination of direct drive motors and mirrors can be used instead of fixed optical lenses. An inert atmosphere is usually used. The vacuum chamber can be completely purged between build cycles, resulting in lower oxygen concentrations and reduced gas leaks.
[0158] Electron beam melting uses a heated bed of metal powder, which is then melted and shaped layer by layer in a vacuum using an electron beam energy source similar to the electron beam energy source in an electron microscope. The metal powder is welded together layer by layer under vacuum.
[0159] Laser Engineered Net Shaping is a powder injection technology that operates by injecting metal powder into a molten metal pool using a laser as the energy source.
[0160] Laser engineered net shaping can be used to manufacture metal parts directly from a solid model designed by computer aided design using metal powder injected into a molten pool created by a focused high power laser beam. Laser engineered net shaping is similar to selective laser sintering, but the metal powder is applied only where material is being added to the part at that time. Note that "net shaping" is meant to encompass "near net" manufacturing.
[0161] The direct metal laser sintering process works by melting fine metal powder in a powder bed layer by layer. The laser provides the necessary energy and the system operates in a protective atmosphere of typically nitrogen or argon.
[0162] Another method utilizes powder injection to provide the material to be deposited. Instead of a powder bed that reacts with the energy beam, powder is injected through a nozzle, which is then melted to deposit the material. The powder can be injected with an inert carrier gas or by gravity feed. A separate shielding gas can be used to protect the molten metal pool from oxidation.
[0163] Directed energy deposition uses focused energy (electron beam or laser beam) to melt the material by melting as it is deposited. Powder or wire feedstock can be used for this process. Powder feed systems (such as laser metal deposition and laser engineered net shaping) blow powder through a nozzle, where the powder is melted by the laser beam on the surface of the part. Laser-based wire feed systems (such as laser metal deposition-wire) feed wire through a nozzle, where the wire is melted by the laser in an open environment (gas around the laser) or in a sealed gas housing or chamber, under inert gas protection.
[0164] Some embodiments utilize wire feedstock and an electron beam heat source to produce near-net-shape parts in a vacuum chamber. The electron beam gun deposits metal layer by layer through the wire feedstock until the part reaches the desired shape. The part is then optionally subjected to final heat treatment and machining. Wires may be preferred over powders for safety and cost reasons. In the present invention, wire feedstock may be produced by melting and solidifying non-spherical particles coated with microparticles, for example, for later use as additive manufacturing feedstock.
[0165] Herderick, “Additive Manufacturing of Metals: A Review,” Proceedings of Materials Science and Technology 2011, Additive Manufacturing of Metals, Columbus, Ohio, 2011, is hereby incorporated by reference for its teachings of various additive manufacturing techniques.
[0166] In any of these additive manufacturing techniques, post-production processes such as heat treatment, light machining, surface finishing, coloring, stamping or other finishing operations can be applied. In addition, several additively manufactured parts can be chemically or physically joined together to produce a final object.
[0167] The additively manufactured functionalized metal alloy preferably has a microstructure that is substantially free of cracks after being recovered in step (e). In some embodiments, the additively manufactured functionalized metal alloy has a microstructure that is substantially free of porous void defects.
[0168] In some embodiments, the additively manufactured functionalized metal alloy is characterized by an average grain size of less than 1 mm, such as about or less than about 500, 400, 300, 200, 150, 100, 75, 50, 40, 30, 20, 15, 10, 5, 4, 3, 2, 1, 0.5, 0.4, 0.3, 0.2, or 0.1 microns.
[0169] In some embodiments, the additively manufactured functionalized metal alloy has a microstructure that is not merely a crystal texture oriented in the additive manufacturing build direction. For example, the solid layers may have different primary growth direction angles relative to each other.
[0170] The additive manufacturing process is not limited in principle to the number of solid layers that can be manufactured. "Multiple solid layers" means at least 2 layers in the functionalized metal alloy manufactured by additive manufacturing, such as at least 10 individual solid layers. The number of solid layers can be much greater than 10, such as about 100, 1000, 10000 or more. The plurality of solid layers can be characterized by an average layer thickness of at least 10 microns, such as about 10, 20, 30, 40, 50, 75, 100, 150 or 200 microns.
[0171] In some embodiments, aluminum is present in the additively manufactured functionalized metal alloy at a concentration of from about 0.1 wt % to about 90 wt %. In some embodiments, copper is present at a concentration of from about 0.1 wt % to about 90 wt %. In these or other embodiments, magnesium is present at a concentration of from about 0.1 wt % to about 90 wt %. In these or other embodiments, at least one of zinc or silicon is present at a concentration of from about 0.1 wt % to about 90 wt %. In some embodiments, the metal alloy further comprises chromium. In some embodiments, scandium is not present in the additively manufactured functionalized metal alloy.
[0172] A metal alloy microstructure with "equiaxed grains" means that at least 90 vol%, preferably at least 95 vol%, and more preferably at least 99 vol% of the metal alloy contains grains that are approximately equal in length, width, and height. In a preferred embodiment, at least 99 vol% of the metal alloy contains grains characterized by a standard deviation of less than 25%, preferably less than 10%, and more preferably less than 5% on each of the average grain length, average grain width, and average grain height. In a metal alloy, the crystals of the metal alloy form grains in a solid. Each grain is a different crystal with its own orientation. The area between the grains is called a grain boundary. Within each grain, the individual atoms form a lattice. In the present disclosure, equiaxed crystals are produced when there are many nucleation sites generated by particles of refined grains contained in the metal alloy microstructure.
[0173] In certain embodiments, the feature of microstructure is further that dispersed microstructure.Dispersed microstructure is usually produced by a large number of dendrites and grain boundaries in microstructure, which are in turn produced by a large number of particles on particle surface.Dispersion degree can be characterized by dispersion length scale, which is calculated as the average length scale in the metal phase between the average spacing and / or particles between particles.In certain embodiments, the dispersion length scale is from about 1 nanometer to about 100 microns, such as from about 10 nanometers to about 10 microns, or about 100 nanometers to about 1 micron.In various embodiments, the dispersion length scale is about, at least about, or at most about 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.5, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 20, 25, 30, 35, 40, 45 or 50 microns.
[0174] The additively manufactured functionalized metal alloy may contain inclusions containing (i) at least one metal from the non-spherical particles and (ii) at least one element from the microparticles. An example of an inclusion is Al3Zr, where the aluminum atoms originate from the non-spherical particles and the zirconium atoms originate from the zirconium-containing microparticles (e.g., Zr or ZrH2 nanoparticles). During the additive manufacturing process, chemical reactions may occur to form Al3Zr inclusions, which themselves may act as inoculants for grain refinement.
[0175] In some embodiments, the particles are lattice matched within ±5% compared to an otherwise equivalent metal alloy without the particles. In certain embodiments, the particles are lattice matched within ±2% or within ±0.5% compared to an otherwise equivalent metal alloy without the particles.
[0176] In some embodiments, the atomic density of the particles is matched within ±25% compared to an otherwise equivalent metal alloy without the particles. In certain embodiments, the atomic density of the particles is matched within ±5% or within ±0.5% compared to an otherwise equivalent metal alloy without the particles.
[0177] Preferably, the microstructure of the functionalized metal alloy manufactured by additive manufacturing is substantially crack-free. A "substantially crack-free" metal alloy microstructure means that at least 99.9 vol% of the metal alloy does not contain linear or curved cracks with a width greater than 0.1 micron and a length greater than 10 microns. In other words, to be considered a crack, the defect must be a void space with a width of at least 0.1 micron and a length of at least 10 microns. Regardless of the width, a void space with a length less than 10 microns but greater than 1 micron can be considered a porous void (see below). A void space with a length of at least 10 microns but a width less than 0.1 micron is a molecular-level gap that is not considered a defect.
[0178] Typically, cracks contain open spaces that may be a vacuum or may contain a gas, such as air, CO2, N2, and / or Ar. Cracks may also contain solid material that is different from the primary material phase of the metal alloy. The undesirable material disposed within the crack may itself contain a higher porosity than the bulk material, may contain a different solid crystalline (or amorphous) phase, or may be an entirely different material, for example, created by impurities during the manufacturing process.
[0179] A three-dimensional configuration can be formed in the final additively manufactured microstructure. "Three-dimensional configuration" means that the particles are not randomly distributed throughout the additively manufactured part. Instead, in the three-dimensional configuration of particles, there is some regularity in the spacing between the particles in space (three dimensions). The average spacing between particles can vary, such as from about 1 particle diameter to about 100 particle diameters or more, depending on the concentration of particles in the material.
[0180] In some embodiments, the three-dimensional configuration of particles in the additively manufactured part is related to the distribution of particles in the starting composition. Such three-dimensional configuration of particles is possible when the dynamics during melting and solidification are controlled so that the integrity and dispersion of the particles are maintained.
[0181] In some embodiments, the particles do not melt and are not significantly dispersed from the original arrangement relative to each other after the one or more metals are melted and then during the solidification process. In certain embodiments, the particles melt, soften (such as become glass) or form a liquid-solution solution after the one or more metals are melted and / or during the solidification process, but are not significantly dispersed from the original arrangement relative to each other. When such particles resolidify (or undergo a phase change) during the solidification of the melt, they assume their original configuration or its approximate coordinates. In some embodiments, whether the particles are melted or not, the particles are ultimately in a three-dimensional configuration, wherein the position of the particles is different from the original configuration, but can be related and therefore predictable based on the starting functionalized raw materials.
[0182] In addition to being substantially crack-free, the metal alloy microstructure may also be substantially free of porous defects. "Substantially free of porous defects" means that at least 99 vol% of the metal alloy contains no porous voids having an effective diameter of at least 1 micrometer.
[0183] Preferably, at least 80 vol%, more preferably at least 90 vol%, even more preferably at least 95 vol%, and most preferably at least 99 vol% of the metal alloy does not contain porous voids having an effective diameter of at least 1 micron. Porous voids with an effective diameter of less than 1 micron are typically not considered defects because they are generally difficult to detect by conventional non-destructive evaluation. Also preferably, at least 90 vol%, more preferably at least 95 vol%, even more preferably at least 99 vol%, and most preferably at least 99.9 vol% of the metal alloy does not contain larger porous voids having an effective diameter of at least 5 microns.
[0184] Typically, the porous voids contain open spaces that may be evacuated or may contain a gas, such as air, CO2, N2, and / or Ar. In some embodiments, the porous voids may be reduced or eliminated. For example, the additively manufactured metal part may be hot isostatically pressed to reduce residual porosity, optionally resulting in a final additively manufactured metal part that is substantially free of porosity defects in addition to being substantially free of cracks.
[0185] In various embodiments, the final additively manufactured article can have a porosity from 0% to about 75%, such as about 5%, 10%, 20%, 30%, 40%, 50%, 60%, or 70%. The porosity can be derived from both the space within the particles (e.g., hollow shapes) and the space outside and between the particles. The total porosity is the source of both porosity.
[0186] Optionally, the porosity can be removed or reduced. For example, a secondary heating and / or pressurization (or other mechanical force) treatment can be performed to minimize the porous voids present in the additively manufactured article. In addition, pores can be removed from the additively manufactured article by physically removing (e.g., cutting away) areas where the porous voids have been isolated.
[0187] In addition to void removal, other post-processing can be performed. For example, forging can improve defects and introduce additional directional strength if desired. Pre-processing (e.g., strain hardening) can produce grain flow oriented in the direction where maximum strength is required.
[0188] The final additively manufactured article may be selected from the group consisting of a structure, a coating, a geometric object, a billet, an ingot, a net shape part, a near net shape part, a weld filler, and combinations thereof. In essence, the geometry of the additively manufactured part is unlimited.
[0189] As mentioned above, the present invention is not limited to the use of metal-containing functionalized materials in additive manufacturing. For example, the metal-containing functionalized materials can also be used in one or more techniques selected from the group consisting of injection molding, sintering, capacitor discharge sintering, isostatic pressing and spark plasma sintering.
[0190] In addition to additive manufacturing, some possible powder metallurgy processing techniques that can be used include, for example, hot pressing, cold pressing, low-pressure sintering, extrusion, pressureless sintering, and metal injection molding. Melting can include induction melting, resistance melting, slag shell melting, arc melting, laser melting, electron beam melting, semi-solid melting, or other types of melting (including conventional and unconventional melt processing techniques). Casting can include, for example, centrifugal casting, pouring casting, gravity casting, investment casting or die casting. Sintering can include, for example, spark discharge, capacitor discharge, resistance, or furnace sintering. Mixing can include, for example, convection, diffusion, shear mixing, or ultrasonic mixing.
[0191] The principles of the present disclosure can be applied to form various functional materials, which contain, consist of, or consist essentially of the metal-containing functionalized materials disclosed herein. Exemplary functional materials include, but are not limited to, ferromagnetic materials, ferrimagnetic materials, paramagnetic materials, magnetocaloric materials, magnetostrictive materials, piezoelectric materials, etc.
[0192] Examples
[0193] Example 1: Mechanical grinding of aluminum alloy.
[0194] Unmodified extruded Al-7075 aluminum alloy rods were obtained as bulk starting material. The Al-7075 rods were mechanically milled using a laboratory scale planetary mill under ambient conditions. The temperature of the mechanical milling was kept below the melting point of Al-7075 (477° C.).
[0195] The first experiment was performed with a single milling / grinding step. Figure 3 is a SEM image showing a single Al-7075 particle resulting from mechanical milling of an extruded rod bulk starting material (scale bar = 1 mm). The characteristic size of the Al-7075 particle is less than 600 microns. The mechanically milled particles are non-spherical.
[0196] A second experiment was conducted in which the grinding intensity was varied by adjusting the parameters of the planetary mill, including the number and spacing of teeth, shear rate, screen size, and number of passes. Figure 4 The particle size distribution of mechanically milled Al-7075 particles at three different milling intensities is shown, labeled 1, 2, and 3 in ascending order of mass intensity. Figure 4 It is revealed that the morphology and particle size can be controlled by the milling process parameters to control the particle size distribution (e.g., Gaussian or unimodal vs. bimodal) and the median characteristic size (D50). In particular, for milling intensity 1, a nearly Gaussian distribution was observed. For milling intensity 2, a bimodal distribution was observed with a main mode of about 400 microns and a secondary mode of about 800 microns. For milling intensity 3, a bimodal distribution was observed with a main mode of about 400 microns and a secondary mode of about 125 microns.
[0197] It was experimentally determined that the bulk density of the powder in Example 1 fell between 49% and 56%.
[0198] Example 2: Cryogenic mechanical grinding of aluminum alloy.
[0199] Unmodified extruded Al-7075 aluminum alloy rods were obtained as bulk starting material.
[0200] The bulk starting material was processed by cryogenic milling (cryomilling) using a laboratory scale cryogenic mill (Retsch GmbH, Haan, Germany). The temperature of cryogenic milling was about -195°C, which is well below the melting point of Al-7075 (477°C).
[0201] Figure 5 is a photograph showing a single Al-7075 particle produced by cryogenically milling an extruded rod bulk starting material (left hand image) compared to a single Al-7075 particle produced by mechanically milling an extruded rod bulk starting material at ambient temperature (right hand image; see Example 1). The cryogenically milled particle is non-spherical. The cryogenically milled particle has a smaller characteristic size than the particle milled at ambient temperature due to reduced ductility.
[0202] Example 3: Chemical pretreatment of aluminum alloy before mechanical grinding.
[0203] A bulk starting material consisting of crushed pieces of extruded Al-7075 aluminum alloy rod was obtained.
[0204] In order to embrittle the metal to reduce ductility, the bulk starting material was exposed to forming gas (Ar / H2, volume ratio of 96% / 4%) using a high temperature furnace at 480°C to reduce the ductility of the aluminum alloy through hydrogen embrittlement. This pretreatment temperature is lower than the liquidus temperature (635°C) of the Al-7075 aluminum alloy.
[0205] After hydrogen pretreatment, the bulk material was then mechanically milled using a laboratory-scale planetary mill at ambient temperature.
[0206] Fig. 6A is a SEM image showing a single Al-7075 non-spherical particle produced by exposure to forming gas followed by mechanical agitation at ambient temperature (scale bar = 200 microns). Figure 6B is a SEM image of a single Al-7075 non-spherical particle showing an embrittled region (scale bar = 50 microns). Figure 6B yes Fig. 6A An enlarged version of .
[0207] Heat treating in the presence of a forming gas embrittles the non-spherical metal alloy powder, thereby enabling the formation of a coarse intermetallic phase that reduces the energy required to mechanically agitate the powder. Figure 6B The formation of a brittle intermetallic secondary phase is evident in the image.
[0208] Example 4: Surface functionalization of non-spherical aluminum alloy particles.
[0209] According to Example 1 ( Figure 4 The grinding intensity of 1) produces aluminum alloy non-spherical particles with a particle size distribution concentrated within 600-700 microns.
[0210] Then, if Fig. 7A (Scale bar = 400 μm) and Figure 7B (Scale bar = 200 microns) As shown in the SEM image of the aluminum alloy microparticles, the aluminum alloy microparticles were functionalized with about 1 vol% of zirconium hydride (ZrH2) microparticles assembled on the surface of all Al-7075 non-spherical particles. Multiple ZrH2 microparticles were observed to cover the surface of the Al-7075 flakes relatively uniformly. The ZrH2 microparticles are intended to serve as an inoculant for the formation of equiaxed crystals during the additive manufacturing process.
[0211] The resulting functionalized powders were then selectively melted and solidified using a Renishaw 500M commercial powder-based laser metal additive manufacturing system (Renishaw PLC, New Mills, United Kingdom). Figure 8 Photograph of a solidified metal alloy part formed by laser melting and solidification of ZrH2 functionalized Al-7075 non-spherical powder (scale bar = 3 mm). As the functionalized powder melts and re-solidifies during the additive manufacturing process, the non-spherical nature of the initial particles no longer exists.
[0212] Despite the low porosity, the structure showed no solidification cracks, indicating incomplete or insufficient application of the ZrH2 inoculant. Figure 8 This indicates that a sufficient concentration and distribution of ZrH2 inoculant was utilized in this example.
[0213] In some embodiments, the present invention improves upon the limitations of the prior art by providing a means for producing powders for metal additive manufacturing or other powder metallurgy processes without the use of gas or water atomization (i.e., without phase change). In these or other embodiments, the present invention improves upon the limitations of the prior art by providing a means for introducing functional particles into metal alloy powders so that previously incompatible (e.g., non-weldable) alloys can now be used in metal additive manufacturing processes. The present disclosure is in no way limited to the reuse of powders or parts that have been compatible with additive manufacturing to date. On the contrary, the principles taught herein enable the use of wrought alloy parts or scrap that are available in large quantities and at low cost.
[0214] In this detailed description, reference has been made to a number of embodiments and drawings in which specific exemplary embodiments of the invention are shown by way of illustration. These embodiments are described in sufficient detail to enable those skilled in the art to practice the invention, and it should be understood that those skilled in the art may make modifications to the various embodiments disclosed.
[0215] When the above method and steps indicate that certain events occur in a certain order, those of ordinary skill in the art will recognize that the order of certain steps can be modified, and such modification is carried out according to variants of the present invention. In addition, certain steps can be carried out simultaneously by parallel processes when possible, or can be carried out successively.
[0216] This specification incorporates by reference U.S. patent application Ser. No. 15 / 880,474 filed on Jan. 25, 2018, U.S. patent application Ser. No. 15 / 880,488 filed on Jan. 25, 2018, and U.S. patent application Ser. No. 15 / 880,466 filed on Jan. 25, 2018.
[0217] All publications, patents, and patent applications cited in this specification are herein incorporated by reference in their entirety to the same extent as if each individual publication, patent, or patent application was specifically and individually set forth herein.
[0218] The above-described embodiments, variations, and accompanying drawings should provide an indication of the practicality and versatility of the present invention. Other embodiments that do not provide all of the features and advantages set forth herein may also be used without departing from the spirit and scope of the present invention. Such modifications and variations are considered to fall within the scope of the present invention as defined by the claims.
Claims
1. A metal-containing functionalized material, comprising: (a) a plurality of non-spherical particles comprising a metal alloy, wherein the non-spherical particles are produced by a process comprising mechanical milling and / or chemical milling of a bulk feedstock comprising a bulk wrought metal alloy, wherein the mechanical milling and / or chemical milling does not induce a solid-liquid phase transition during conversion of the bulk wrought metal alloy into the non-spherical particles, the non-spherical particles being smaller than a length scale of the bulk feedstock; and (b) a plurality of microparticles physically and / or chemically assembled on the surface of the non-spherical particle, wherein the microparticles are selected from the group consisting of metals, metal alloys, metal carbides, metal nitrides, metal borides, metal hydrides, metal oxides, metal sulfides, ceramics, and combinations thereof, wherein the microparticles are compositionally different from the non-spherical particles, wherein the particles have an average particle size that is different from an average non-spherical particle size of the non-spherical particles; and The non-spherical particles are characterized by a packing density ranging from 49% to 56%.
2. The metal-containing functionalized material according to claim 1, wherein: The non-spherical particles are selected from whiskers, needles, debris, deformed ribbons, rods, fibers, oblate spheroids, prolate spheroids, parallelepipeds, rhombuses, rectangular prisms, flakes, polyhedral particles, randomly shaped particles and / or combinations thereof.
3. The metal-containing functionalized material according to claim 1, wherein: The stacking efficiency is from 49% to 55%.
4. The metal-containing functionalized material according to claim 1, wherein: The stacking efficiency is from 55% to 56%.
5. The metal-containing functionalized material according to claim 1, wherein: The non-spherical particles are characterized by a median particle size (D50) of from 10 microns to 10 millimeters.
6. The metal-containing functionalized material according to claim 1, wherein: The average microparticle size is smaller than the average non-spherical particle size.
7. The metal-containing functionalized material according to claim 6, wherein: The average microparticle size is at least an order of magnitude smaller than the average non-spherical particle size.
8. The metal-containing functionalized material according to claim 1, wherein: The average particle size is from 5 nanometers to 100 micrometers.
9. The metal-containing functionalized material according to claim 1, wherein: The microparticles form a continuous coating on the non-spherical particles.
10. The metal-containing functionalized material according to claim 1, wherein: The microparticles form a discontinuous coating on the non-spherical particles.
11. The metal-containing functionalized material according to claim 1, wherein: The non-spherical particles contain a metal selected from the group consisting of aluminum, titanium, cobalt, chromium, iron, copper, tungsten, magnesium, niobium, nickel, tantalum, silicon, vanadium, gold, silver, platinum, palladium, iridium, rhenium, zinc, cerium, molybdenum, zirconium, hafnium, and alloys or combinations thereof.
12. The metal-containing functionalized material according to claim 1, wherein: The microparticles contain a metal selected from the group consisting of aluminum, titanium, cobalt, zinc, tin, chromium, bismuth, neodymium, dysprosium, erbium, samarium, praseodymium, gadolinium, ytterbium, lanthanum, boron, lithium, calcium, strontium, scandium, yttrium, manganese, rhenium, iridium, lead, carbon, indium, gallium, iron, copper, tungsten, magnesium, niobium, nickel, tantalum, silicon, vanadium, gold, silver, palladium, platinum, cerium, zirconium, hafnium; carbides, nitrides, borides, hydrides, intermetallic compounds, oxides, or sulfides thereof; and combinations thereof.
13. The metal-containing functionalized material according to claim 1, wherein: The combined concentration of the non-spherical particles and the microparticles is from 50 vol% to 100 vol% of the metal-containing functionalized material.
14. A method for producing a metal-containing functionalized material, the method comprising: (a) providing a bulk raw material comprising a bulk forging metal alloy; (b) mechanically and / or chemically milling the bulk feedstock to produce a plurality of non-spherical particles comprising a metal alloy, wherein the mechanical and / or chemical milling does not induce a solid-liquid phase transition during the conversion of the bulk wrought metal alloy into the non-spherical particles, wherein the non-spherical particles are smaller than a length scale of the bulk feedstock, and wherein the non-spherical particles are characterized by a packing density of from 49% to 56%; (c) providing microparticles selected from the group consisting of metals, metal alloys, metal carbides, metal nitrides, metal borides, metal hydrides, metal oxides, metal sulfides, ceramics, and combinations thereof, wherein the microparticles are compositionally different from the non-spherical particles; and (d) physically and / or chemically assembling the microparticles onto the surface of the non-spherical particles, wherein the microparticles have an average particle size that is different from an average non-spherical particle size of the non-spherical particles.
15. The method of claim 14, wherein: The mechanical grinding and / or chemical grinding utilizes mechanical milling selected from the group consisting of ball milling, crushing, grinding, pulverizing, grinding, high shear mixing, vibration mixing, acoustic mixing, and combinations thereof.
16. The method of claim 14, wherein: The mechanical milling and / or chemical milling utilizes chemical milling selected from the group consisting of etching, dealloying, acid treatment, alkali treatment, and combinations thereof.
17. The method of claim 14, wherein: The bulk material is in the form of plates, sheets, ingots, extrudates, or combinations thereof.
18. The method of claim 14, wherein: The bulk stock includes forgings, castings, semi-finished parts, machine shop prototypes, inferior parts, rejected parts, damaged parts, metal scraps, machine shavings, recycled parts, or combinations thereof.
19. The method of claim 14, wherein: The non-spherical particles include whiskers, needles, rods, fibers, oblate spheroids, prolate spheroids, parallelepipeds, rhombuses, rectangular prisms, flakes, polyhedral particles, randomly shaped particles, and / or combinations thereof.
20. The method of claim 14, wherein: The non-spherical particles are characterized by a median particle size (D50) of from 10 microns to 1 millimeter.
21. The method of claim 14, wherein: The average particle size is from 5 nanometers to 100 micrometers.
22. The method of claim 14, wherein: The average microparticle size is smaller than the average non-spherical particle size.
23. The method of claim 14, wherein: The non-spherical particles contain a metal selected from the group consisting of aluminum, titanium, cobalt, chromium, iron, copper, tungsten, magnesium, niobium, nickel, tantalum, silicon, vanadium, gold, silver, cerium, molybdenum, zirconium, hafnium, and combinations thereof.
24. The method of claim 14, wherein: The microparticles contain a metal selected from the group consisting of aluminum, titanium, cobalt, zinc, tin, chromium, iron, copper, tungsten, magnesium, niobium, nickel, tantalum, silicon, vanadium, gold, silver, palladium, platinum, cerium, zirconium, hafnium; carbides, nitrides, borides, hydrides, oxides, or sulfides thereof; and combinations thereof.
Citation Information
Patent Citations
Methods for nanofunctionalization of powders, and nanofunctionalized materials produced therefrom
US20180214944A1
Additive manufacturing with nanofunctionalized precursors
US20180214949A1
Aluminum alloys with grain refiners, and methods for making and using the same
US20190032175A1
Nanoparticle composite welding filler materials, and methods for producing same
CN110461535A